A mason-inspired pattern generator for historic masonry structures using quality indexes - Szabó, Simon (2024)
A considerable amount of historic masonry structures (HMS) are composed of irregular stone. However, few studies have systematically investigated the influence of masonry patterns (or masonry unit arrangements) on structural behaviour. The main difficulty stems from the pattern acquisition and the definition of adequate parameters that correlate the pattern with the structural behaviour. To this aim, this paper presents a stochastic 2D coursed-rectangular masonry pattern generator that incorporates geometric quality indexes (QI) to generate patterns with consistent masonry quality and structural behaviour. The generator’s input parameters separately consider the available stone units and the "virtual mason"’s skill level to cover the range of possible pattern qualities. Finally, micro limit analysis simulations show how deviation from the "rules of art" reduces strength capacity by up to 30%. Furthermore, it has been discussed how masonry patterns generated with selected QI-s show consistent structural behaviour, e.g. reducing the coefficient of variation of the strength capacities by 15%.